2013
DOI: 10.1002/glia.22618
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension controls the expression of the monocarboxylate transporter MCT4 in cultured mouse cortical astrocytes via a hypoxia‐inducible factor‐1α‐mediated transcriptional regulation

Abstract: The monocarboxylate transporter MCT4 is a high capacity carrier important for lactate release from highly glycolytic cells. In the central nervous system, MCT4 is predominantly expressed by astrocytes. Surprisingly, MCT4 expression in cultured astrocytes is low, suggesting that a physiological characteristic, not met in culture conditions, is necessary. Here we demonstrate that reducing oxygen concentration from 21% to either 1 or 0% restored in a concentration-dependent manner the expression of MCT4 at the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 47 publications
(65 reference statements)
1
48
0
Order By: Relevance
“…Low oxygen tension is a potent differentiation inducer of numerous cell types and an effective stimulus of gene expression (Rosafio and Pellerin, 2013). Thus, we evaluated the effects of reduced oxygen tension on HPDLSCs proliferation and the influence on osteogenic capability.…”
Section: Discussionmentioning
confidence: 99%
“…Low oxygen tension is a potent differentiation inducer of numerous cell types and an effective stimulus of gene expression (Rosafio and Pellerin, 2013). Thus, we evaluated the effects of reduced oxygen tension on HPDLSCs proliferation and the influence on osteogenic capability.…”
Section: Discussionmentioning
confidence: 99%
“…MCT4 expression was previously shown to be up-regulated, together with many glycolytic enzymes such as transcription factor hypoxia-inducible factor-1<alpha> (HIF-1<alpha>) [9]. The promoter region of the MCT4 gene contains hypoxiaresponse elements, to which HIF-1<alpha> can bind to activate transcription [27].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter region of the MCT4 gene contains hypoxiaresponse elements, to which HIF-1<alpha> can bind to activate transcription [27]. We previously demonstrated that neuronalenriched cultures were non-resistant to OGD in the absence of astrocytes, while OGD up-regulated MCT4 expression at the mRNA and protein levels via HIF-1<alpha>-mediated transcriptional regulation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact cellular sources of such IH-induced detrimental effects are still incompletely defined, it is likely that a portion of such deleterious effects is ascribable to activation of astroglia and subsequent loss of buffering functions that ultimately contribute to pathological processes, such as increased glial proliferation and microglial activation (63,179). Astroglial and microglial cells play critical roles in regional blood flow regulation and inflammatory processes in the brain as well as critical coordination of bioenergetics through lactate transport (22,140,155). Activated microglia express high levels of the inducible isoform of NOS (iNOS) and COX-2, with both enzymes initiating pathways ultimately leading to generation and propagation of ROS.…”
Section: Maladaptation To Ih: Pathological Effectsmentioning
confidence: 99%